PLACE AND IMPORTANCE OF EMBROIDERY ART - Akhmedova Nozimakhon (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Uzbek folk art occupies a special place in human culture. Examples of high art created by masters of Uzbek folk art, various carvings, textile ornaments, are world famous both in the past and now, in museums of applied art and ethnography in different cities of the world. Is being shown. All this is a source of great pride for us, the present generation. And the works created by painters, sculptors, architects, potters, composers, writers and other creative people are undoubtedly called works of art. Whatever form art takes, it manifests itself as spiritual beauty and goodness that affects people’s emotions and psyche. Each creator is sought after differently, works differently. That is why there are specific types of art.